Pengaruh Variabel-variabel Kualitas Pelayanan terhadap Kepuasan Anggota Unit Pertokoan Koperasi Pegawai Republik Indonesia Universitas Jember - Handayani, Siswi Tri; Wahyudi, Edy; Poerwanto, . (e-SOSPOL (e-ISSN: 2355-1798), 2014)
This research is intended to identify the effects of the variables of service quality on customer satisfaction quality of shopping unit at Koperasi Pegawai Republik Indonesia (Republic of Indonesia Employee Cooperative) of Jember University. Service quality is the main approach to providing satisfaction to the consumers. In line with this, companies need to understand how consumers perceive the quality and the level of quality they expect. Companies should necessarily work maximally to fulfill the customers quality expectation. This research was to identify service quality to costumer satisfaction. Samples of the research were 97 respondents who were the cooperative members of shopping at shopping unit while the research was being conducted. Variables of th researh were tangibility, reliability, responsiveness, assurance and empathy. The research results showed that the independent variables consisting of responsiveness, reliability, assurance, empathy and tangibility affected the dependent variable namely customer satisfaction. The results of the research indicated that the most highly influential variable of the service quality to member satisfaction was responsivenes and the least influential one was assurance. Keywords: retail businesses, customer satisfaction, cooperative, service quality